Social Psychological Origins of Conspiracy Theories: The Case of the Jewish Conspiracy Theory in Malaysia - Swami, Viren (Frontiers in Psychology, 2012)
Two studies examined correlates of belief in a Jewish conspiracy theory among Malays in Malaysia, a culture in which state-directed conspiracism as a means of dealing with perceived external and internal threats is widespread. In Study 1, 368 participants from Kuala Lumpur, Malaysia, completed a novel measure of belief in a Jewish conspiracy theory, along with measures of general conspiracist ideation and anomie. Initial analysis showed that the novel scale factorially reduced to a single dimension. Further analysis showed that belief in the Jewish conspiracy theory was only significantly associated with general conspiracist ideation, but the strength of the association was weak. In Study 2, 314 participants completed the measure of belief in the Jewish conspiracy theory, along with measures of general conspiracist ideation and ideological attitudes. Results showed that belief in the Jewish conspiracy theory was associated with anti-Israeli attitudes, modern racism directed at Chinese, right-wing authoritarianism, and social dominance orientation. General conspiracist ideation did not emerge as a significant predictor once other variables had been accounted for. These results suggest that there may be specific cultural and social psychological forces that drive belief in the Jewish conspiracy theory within the Malaysian context. Specifically, belief in the Jewish conspiracy theory among Malaysian Malays appears to serve ideological needs and as a mask for anti-Chinese sentiment, which may in turn reaffirm their perceived ability to shape socio-political processes.